2013
DOI: 10.15602/1983-9480/cmbs.v15n30p65-74
|View full text |Cite
|
Sign up to set email alerts
|

Polifarmácia Utilizada por Idosos Residentes em Instituições de Longa Permanência do Município de Viamão/RS

Abstract: Fazer um levantamento da quantidade de medicamentos administrados por idoso residente de instituições de longa permanência para idosos. Avaliar as doenças mais incidentes entre estes idosos, observar o perfil do idoso, além de discutir o papel do farmacêutico. Metodologia: Trata-se de um estudo observacional transversal. Os dados foram obtidos através de questionários com perguntas abertas e fechadas aos cuidadores de 85 idosos residentes nas instituições de longa permanência para idosos do município de Viamão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…One study found that captopril was among the drugs most commonly used by elderly people living in a long-term institution, then totaling 31.7%. 46 Associated with the aging population, there is an increase in the prevalence of chronic-degenerative diseases associated with age, cardiovascular diseases. 43 The drugs most frequently used by elderly chronic users of omeprazole are related to the diseases most prevalent in this study, already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that captopril was among the drugs most commonly used by elderly people living in a long-term institution, then totaling 31.7%. 46 Associated with the aging population, there is an increase in the prevalence of chronic-degenerative diseases associated with age, cardiovascular diseases. 43 The drugs most frequently used by elderly chronic users of omeprazole are related to the diseases most prevalent in this study, already mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência da HAS assemelha-se a de outras evidências científicas realizadas também com idosos residentes em ILPI (OLIVEIRA PC e NOVAES MRCG, 2013; RIBEIRO NP, et al, 2013). Essa doença constitui a morbidade mais frequente nos maiores de sessenta anos, sendo que cerca de dois terços dos idosos brasileiros são portadores de HAS, sua prevalência aumenta com a idade e os tratamentos inadequados A sétima Diretriz Brasileira de Hipertensão Arterial da Sociedade Brasileira de Cardiologia (SBC) (2016), descreve que existe uma associação direta entre o envelhecimento e a prevalência de HAS e essa condição clínica pode ser agravada por outros fatores de risco dentre eles a presença de diabetes, que apresentou uma taxa de prevalência considerável no estudo.…”
Section: Variávelunclassified
“…Therefore, LSIs no longer assume a role of shelter to support social assistance and health care. Another important aspect of the aging process in the current context is the relationship between increased comorbidities and intensify drug use 7 .…”
Section: Introductionmentioning
confidence: 99%